Educação e desenvolvimento no estado brasileiro contemporâneo: a visão do STF em 30 anos da constituição - Otaviano, Luiz Renato Telles (2019)
Brazil' s Federal Constitution , dated of 1988 (CF/1988) established a project of social transformation guided to the construction of a free, fair and solidary society, a fundamental objective expressed in its article 3°. The realization of this project is linked to the promotion of national development , thought beyond its economic aspect, as proposed by Celso Furtado, to include the social, cultural and political dimensions as well. ln this regard, the national development project incorporated by the CF / 88 must be focused on the transformation of the social structures , emphasizing the value of the human factor. For this reason, the implementation of social rights, in particular the right of education, imposes itself as one of the key strategic strands for national development. It is true that it is the Executive and Legislative Powers competence to formulate and implement the public policies, aimed to promote social rights in general, including educational ones. However, with the enactment of CF/1988, the judiciary was called to decide about numerous issues that had only been resolved within the policy framework. The present research, based on the analysis of the concept of development through bibliographic research, proposes to perform an empirical analysis of a representative set of Supreme Court (STF) decisions on the right of education, in the time frame from 1988 to 2018, seeking to identify whether the reasoning used by the Court adopts, as a decisive parameter, the fundamental objectives that inform CF/1988, summarized in the duty to promote national development. The hypothesis that will be challenged is that the decision model adopted by the Supreme Court does not necessarily binds its performance to such parameters, and the limits of its action are not clear, and there is even the possibility of rediscussing issues that had already been decided.